2010
DOI: 10.1097/rct.0b013e3181da3671
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Diffusion-Weighted Magnetic Resonance Imaging in the Characterization of Hepatocellular Carcinomas and Dysplastic Nodules in Cirrhotic Liver

Abstract: Diffusion-weighted MRI can provide additional information to differentiate HCC from DN. Combined with CE-MRI, DWI allows improved characterization of HCC versus DN in cirrhotic liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 34 publications
5
69
1
1
Order By: Relevance
“…Therefore, the exact value of restriction in diffusion can be assessed by ADC measurements of the lesions 20 . ADC and ADC ratio values of HCCs were significantly lower than DN in our study but lower than previously published reports 3,19 . We found an ADC value of ≤ 1.316x10 -3 mm²/s and an ADC ratio of ≤ 0.94 as the best cut-off points.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Therefore, the exact value of restriction in diffusion can be assessed by ADC measurements of the lesions 20 . ADC and ADC ratio values of HCCs were significantly lower than DN in our study but lower than previously published reports 3,19 . We found an ADC value of ≤ 1.316x10 -3 mm²/s and an ADC ratio of ≤ 0.94 as the best cut-off points.…”
Section: Discussioncontrasting
confidence: 55%
“…In recent studies on DWI to evaluate hyperintensity of HCCs compared to the surrounding hepatic parenchyma, different b values were used. Piana et al found a sensitivity value of 72% or 82% depending on the reader and Xu et al 19 found a value of 67.5% with a b factor of 500 s/mm², while Vandecaveye found a value of 95.2% with a b factor of 600 s/mm² on DWI 3,12 . A consensus conference on DWI in cancer imaging stated that higher b values are needed in high vascular tissues 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taouli et al first showed that ADC values can be used to differentiate between benign and malignant lesions in liver. 20,21 After this, few studies 23,24 were done to differentiate between benign and malignant hepatic lesions and also to differentiate between various grades of HCC. Nasu et al, 19 Piana et al, 15 and Saito et al 25 showed that there exists no relationship between ADC values and histopathological grades of HCC, whereas Heo et al 26 and Nishie et al 27 said that the ADC values of HCC had an inverse correlation with the degree of differentiation.…”
Section: Role Of Diffusion Weighted Imaging For Hepatocellular Carcinmentioning
confidence: 99%
“…As a consequence of hepatocyte uptake, normal liver areas exhibit T1 shortening, whereas focal liver lesions without hepatocytes do not. Gd-EOB-DTPA has been shown to be useful in the detection of focal malignant liver lesions, including hepatocellular carcinoma and metastasis (16,17). In the present patient, hepatic EAML showed homogeneous and significantly lower signal intensity at the hepatobiliary phase at 30 min post-Gd-EOB-DTPA injection compared with the normal liver parenchyma.…”
Section: Discussionmentioning
confidence: 62%